Multi-Institutional Regional Otolaryngology Bootcamp. (June 2020) - Cervenka, Brian P.; Hsieh, Tsung-yen; Lin, Sharon; Bewley, Arnaud
Introduction: In order to increase junior resident physician proficiency and improve patient safety, simulation-based procedural training courses, or bootcamps, have been become an emerging educational tool. Objectives: To compare pre- and post-course confidence levels and to assess station efficacy after completion of our single day bootcamp. Methods: We developed the University of California (UC) Davis otolaryngology bootcamp, a single day course including six cadaveric task trainer stations and four simulations. The six task trainer stations included (1) Epistaxis, (2) Cricothyrotomy/tracheostomy, (3) Peritonsillar abscess/auricular hematoma, (4) Nasal bone reduction/zygoma reduction/lateral canthotomy/canalicular trauma and probing, (5) Local nerve blocks, and (6) Soft tissue reconstruction. The simulations comprised of airway fire during tracheostomy, pediatric respiratory code during airway evaluation, dislodged pediatric tracheostomy tube in the ICU, and angioedema in the emergency department with inability to intubate or ventilate. Junior residents from multiple locoregional institutions were recruited to participate. Pre- and post-course Likert surveys assessing participant confidence and station efficacy were collected and analyzed. Results: There was a statistically significant increase in resident confidence levels for all task trainer stations. All stations had a station efficacy Likert score average of 4 "very effective" or 5 "most effective." Conclusion: A multi-institutional, locoregional, simulation-based bootcamp can be a valuable adjunct to junior resident training. It can promote camaraderie, pool limited resources, and may be cost-effective.